Cluster Development in Romania in a European Context - Florica ȘTEFĂNESCU; Melania POP; Olimpia BAN; Delia Bekesi; Csaba BEKESI (Communications of International Proceedings, 2022)
Today, cluster development is proving to be an option for more and more entrepreneurs given the competitive and sustainable potential of clusters. Our paper aims to bring to the attention of specialists the cluster development in Western and Eastern Europe, including Romania, to highlight and explain the characteristics of Romanian clusters. For this purpose, we resorted to a statistical analysis of the types of clusters already existing in the EU, to the analysis of some archival documents from the history of Romania and of the characteristics of the clusters in the Eastern European countries. The main results consisted in identifying the clusters by regions of the EU and Romania, in capturing similarities between organizational structures in communist Romania and contemporary clusters, as well as in highlighting the originality of the Romanian cluster type.
Keywords: clusters; EU; Romania; cluster type structures in communism; cluster model